The Environment and International Relations - Imber, Mark; Vogler, John (Taylor & Francis, 1996)
Environmental issues and questions of global change are now firmly established on the international political agenda. This book provides a wide-ranging survey of the current treatment of environmental issues in international relations. This book begins by looking at the relevance of the different theoretical approaches current in international relations to the study of the environment. It analyzses a wide range of approaches from the debate between neo-realism and liberal institutionalism to the significant connections between gender and global environmental change. The book goes on to consider a range of key international processes, discussing the monitoring and implementation of environmental agreements, the place of ideology in negotiations and the role of international organisations.